KEPENTINGAN INDONESIA TERHADAP TIMOR LESTE DALAM KERJA SAMA SELATAN-SELATAN (2016-2018) - Gusti, Chensy Silvia; Saeri, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Indonesia made Timor Leste a priority country in South-South Cooperation in terms of the number of programs provided by Indonesia to Timor Leste. This policy demonstrates Indonesia's interest in Timor Leste in South-South Cooperation. The purpose of this study is to determine Indonesia's interests in Timor Leste in the framework of South-South Cooperation 2016-2018. The pluralism perspective used in this study views that strong relationships between countries are influenced by dependency factors. This study uses the theory of foreign policy in which policy making is influenced by national interests. This research uses a qualitative-descriptive method through literature study. South-south cooperation is a collective action between developing countries in the form of economic, socio-cultural, and technical cooperation such as the exchange of knowledge and technology. The perspective of actors and national interests are internal factors in international cooperation. Based on data analysis, Indonesia has achieved political, economic and defense and security interests in making Timor Leste a priority country to receive South-South Cooperation. The protection of Indonesian citizens and national integrity, accelerating compliance with border regulations, expanding Indonesia's influence in international forums, and maintaining Indonesia's influence as the main importing country in Timor Leste are in Indonesia's interests towards Timor Leste in South-South Cooperation. Several excellent programs that have been given by Indonesia to Timor Leste in the 2016-2018 period include the exchange of knowledge in improving entrepreneurial education, building national roads and building the capacity of police personnel.Keywords: South-south Cooperation, Foreign Policy, National Interest.